Imunodiagnóstico da ascaridíase humana: uma nova abordagem sorológica utilizando a tecnologia IgY - Lopes, Camila de Almeida (2018)
Human ascariasis is a neglected tropical disease of great relevance to public health and is considered the most frequent helminthiasis in poor regions. Accurately diagnosing the presence of this parasitosis has been challenging due to limitations of current diagnostic methods. Immunoglobulin Y (IgY) technology is an alternative for the production of highly specific and profitable antibodies with several advantages, i.e. the keeping of chickens is affordable, the animals are easily handled and it is very effective. This study aimed to produce, fractionate, purify, characterize and apply polyclonal IgY antibodies anti-Ascaris suum in the immunodiagnosis of human ascariasis. Five immunisations with total saline extract of A. suum adult life forms were performed at 14-day intervals in hens (Gallus gallus domesticus) of the Isa Brown line. Eggs and blood samples were collected weekly and fortnightly, respectively, to monitor the production of antibodies. IgY immunoglobulin obtained from eggs was purified in a HiTrap IgY Purification affinity column in a complete ÄKTA prime plus chromatography system. The specificity of antibodies was confirmed by dot-blot, SDS-PAGE 12%, kinetic enzyme-linked immunosorbent assay (ELISA), avidity ELISA, immunoblotting and indirect immunofluorescence antibody tests. Application in the diagnosis was performed through detection of immune complexes, in human serum samples, by sandwich ELISA. Peaks of IgY anti-A. suum production occurred at six and eight weeks. The antibodies showed high avidity levels after the second dose of immunisation, ranging from 64% to 93% and a mean avidity index of 78.30%. Purified IgY recognised 12 bands of proteins of A. suum saline extract in the immunoblotting assay. Eggs, the uterine portion and cuticles of A. suum female adult were reactive in immunofluorescence by IgY. The detection of immune complexes showed diagnostic values of 80% sensitivity and 90% specificity. In conclusion, parasite-specific IgY antibodies have been shown to be a potential immunodiagnostic tool with promising future applications in human ascaridiasis therapy.